Pojmovanje trajnosti skozi porabniške prakse - Podnar, Klement (Akademija MM, 2019)
In this paper, we explore how individu-als in the context of shopping habits and every-day consumption practices experience and make sense of sustainable consumption. In doing so, we follow newer approaches towards sustainable consumption that go beyond classical cognitive frameworks and try to understand sustainable consumption through everyday social practices. Following this, we try and uncover the complexity of the problem and discover the gaps that arise between what individuals think and how they act. The empirical part is based on a qualitative approach; the data were collected in spring of 2018 through an online asynchronous group discussion. The findings show that the buying practices of individuals partly demonstrate their sustainable attitude, but individuals do not always make a connection between them. The results also indicates that sustainability is not necessarily reflected into actual practices, but is often based on rather abstract representations that are not realized in everyday life. However, it can be concluded that the practices and representations of sustainability also overlap in some cases. In the end, some implications for practice are proposed.
Keywords: Consumer behavior; Consumption; Nakupovanje; Potrošnja; Shopping; Sustainable development; Trajnostni razvoj; Vedenje potrošnikov